Implications of Intravital Imaging of Murine Germinal Centers on the Control of B Cell Selection and Division - Binder, Sebastian C.; Meyer-Hermann, Michael (Frontiers in Immunology, 2016)
Intravital imaging of antibody optimization in germinal centre (GC) reactions has set a new dimension in the understanding of the humoral immune response during the last decade. The inclusion of spatio-temporal cellular dynamics in the research on GCs required analysis with agent-based mathematical models. Here, we integrate the available intravital imaging data from various research groups and incorporate these into a quantitative mathematical model of GC reactions and antibody affinity maturation. Interestingly, the integration of data concerning the spatial organisation of GCs and B cell motility allows to draw conclusions on the strength of the selection pressure and the control of B cell division by T follicular helper cells.